Direct retrospective measurement of therapeutic changes: An example using the Czech version of the Questionnaire of Personal Changes (Q-PC) - Řiháček, Tomáš; Macková, Kateřina; Cígler, Hynek (Psychotherapy research, 2025)
Objective: The study aimed to test the psychometric properties of the Czech translation of the Questionnaire of Personal Changes (Q-PC), a measure designed for retrospective (direct) measurement of change in psychotherapy.Methods: A sample of group psychotherapy clients (N = 222) and a nonclinical sample (N = 167) sample were used. Clients in the clinical sample were administered the Q-PC in addition to several pre-post outcome measures. Confirmatory factor analysis, correlational analysis, and structural equation modeling were used to test the Q-PC's factor structure, longitudinal measurement invariance, reliability, convergent validity, sensitivity to change, and other psychometric properties.Results: The Q-PC demonstrated a unidimensional structure that was strictly invariant between two follow-up measurement waves. The measure also demonstrated excellent reliability and sensitivity to change and good convergent validity. Furthermore, it demonstrated a similar relationship to baseline severity as the pre-post outcome measures.Conclusions: The retrospective measurement of change is a promising approach that has the potential to complement the traditional pre-post measurement of change.
Keywords: Surveys and Questionnaires; skupinová psychoterapie; Humans; lidé středního věku; sensitivity to change; Female; mladý dospělý; dospělí; factor analysis; positive change bias; lidé; direct measurement of change; reprodukovatelnost výsledků; průzkumy a dotazníky; Psychotherapy, Group; duševní poruchy; Adult; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Retrospective Studies; Psychometrics; Czech Republic; Mental Disorders; Young Adult; retrospektivní studie; Česká republika; mužské pohlaví; psychometrie; retrospective measurement of change; Questionnaire of Personal Changes